Carta de Manuel F. Rossy a Willis Sweet y Roberto H. Todd - Todd, Roberto H.; Rossy, Manuel F.; Sweet, Willis (My University, 1916)
Carta relacionada al Proyecto Jones.
Keywords: Partido Republicano (Puerto Rico); Republican party. Puerto Rico.; Jones Act, 1917 (P.R.)